Beetroot juice supplementation increases concentric and eccentric muscle power output. Original investigation. Issue 1 (January 2021) - Rodríguez-Fernández, Alejandro; Castillo, Daniel; Raya-González, Javier; Domínguez, Raúl; Bailey, Stephen J.
Abstract: Objectives: Beetroot juice (BJ) supplementation has been reported to enhance skeletal muscle contractile function; however, it is currently unclear whether BJ supplementation elicits comparable improvements in power output during different types of skeletal muscle contractions. The purpose of the current study was to assess the effect of BJ supplementation on power output during concentric (CON) and eccentric (ECC) muscle contractions during a half-squat. Design: In a randomized, double-blind placebo-controlled crossover design, eighteen adult males (age: 22.8 ± 4.9 y) completed two experimental testing sessions 2.5 h following the acute ingestion of 140 mL nitrate-rich BJ concentrate or a placebo. Methods: Each experimental session comprised four sets of eight all-out half-squat repetitions with each set completed with a different moment intertia (0.025, 0.050, 0.075 and 0.100 kg·m −2 ). Results: Compared to placebo, BJ supplementation increased mean power output (MP) during the CON (ES: 0.61–1.01) and ECC (ES: 0.54–0.89; all p < 0.05) movement phases to a similar extent. Moreover, comparable increases in peak power output (PP) during the CON (ES: 0.86–1.24) and ECC (ES: 0.6–1.08; all p < 0.05) movement phases were observed following BJ supplementation. Conclusion: Acute BJ supplementation increased mean and peak lower limb power output in the concentric and eccentric movement phases of a half-squat. These findings improve understanding of the effects of BJ supplementation on skeletal muscle contractile function and might have implications for enhancing sports performance in events where muscle power output is a key performance determinant.